Enumeration of Floor Plans Based on a Zero-Suppressed Binary Decision Diagram. (March 2015) - Takizawa, Atsushi; Miyata, Yushi; Katoh, Naoki
This paper presents novel algorithms for enumerating architectural floor plans. The enumeration approach attempts to generate all feasible solutions that satisfy given constraints. Therefore, such a method might usefully reveal the potential diversity of Open Building floor plans. However, combinatorial enumeration solutions easily explode even for small problem sizes. We represent a space by a set of cells and organize some cells into polyomino-like configurations. We then enumerate all cell combinations that can be tiled in the given space using an efficient search algorithm for combinatorial problems. We also propose queries for extracting specific floor plans that satisfy additional constraints from all enumerated floor plans without re-enumeration. Our approach solves a 56-cell configuration space within a realistic timeframe.